Benefisiasi bijih emas dan perak kadar rendah menggunakan palong dan metode flotasi - Widi Astuti; Kusno Isnugroho; Fika Rofiek Mufakhir; Ulin Herlina; Isti Nurjanah (Jurnal Rekayasa Proses, 2018)
Beneficiation of low-grade gold and silver ores were investigated by gravity concentration flotation methods. The ores were obtained from Way Kanan Region and Mount Burhan in Province of Lampung. In this study, gravity concentration in sluice box and flotation were performed in sequence. Effect of particle size was investigated in gravity concentration by sluice box. Furthermore, effect of various parameters in flotation operation such as concentration of collector, ore particle size, and processing time were studied. Gravity concentration in sluice box indicated that the highest recovery of gold and silver were 76.52% and 94.83%, respectively when using ore particle size of 100+150 mesh. Flotation experiments showed that the maximum recoveries of gold and silver obtained were 98.33% and 86.42%. The conditions to obtain maximum recovery in this study were -100+150 mesh of ores particle size, 25 mL/kg concentration of collector, and 25 minutes of processing time.